Géneros de texto e as dimensões do suporte - Rosa, Rute; Gonçalves, Matilde (Revista da Associação Portuguesa de Linguística, 2020)
Situated within text and discourse linguistics, this paper focuses on presentation and discussion of the relations between medium and text genres. Firstly, a categorization of the dimensions of the medium is presented. Finally, based on a qualitative analysis, this article discusses the role of medium in different textual genres - scientific article, medication package insert, interview, and graffiti.